Upaya Meningkatkan Soft Skill Mahasiswa Di Perguruan Tinggi - Milawati; Yohannes Don Bosko; Elisabeth Fransiska Bowleyn; Leonard Siahaan (Sekolah Tinggi Manajemen Pariwisata dan Logistik Lentera Mondial, 2023)
ABSTRACT In the context of competition in the world of work, quality human resources are needed. Higher education as one of the institutions that produce and develop human resources has an obligation to prepare and improve its graduates so they can take part in the competition mentioned above. Therefore, universities need to provide hard skills and improve students' soft skills. Hard skills are obtained through lecture material related to the cognitive domain, while soft skills are to develop the affective and psychomotor domains, which can be obtained by participating in extra-curricular activities through English, computer courses, participating in student activities, participating in apprenticeship programs, studying entrepreneurship, and the use of innovative learning methods. Keywords: Softskill, Student Affairs.